Second-line therapy in diffuse large B-cell lymphoma (DLBCL): treatment patterns and outcomes in older patients receiving outpatient chemotherapy. Issue 5 (4th May 2017) - Danese, Mark D.; Griffiths, Robert I.; Gleeson, Michelle L.; Dalvi, Tapashi; Li, Jingyi; Mikhael, Joseph R.; Deeter, Robert; Dreyling, Martin
Abstract: Using SEER-Medicare linked data we identified elderly patients diagnosed with diffuse large B-cell lymphoma (DLBCL) between January 2000 and December 2007 who received second-line outpatient chemotherapy for relapsed or refractory disease. Second-line regimens were classified into three mutually exclusive groups: aggressive, conventional, and palliative. Of the 632 (426 relapsed, 206 refractory) patients in the cohort, 27.8% received aggressive second-line therapy, 39.1% received conventional therapy, and 33.1% received palliative therapy. There were no differences in survival by type of therapy received, either for relapsed or refractory patients, although the patient risk profile differed significantly. However, duration of remission, male gender, and anemia at diagnosis were important predictors in relapsed patients, and male gender, B-symptoms, comorbidity burden, and poverty status were important predictors in refractory patients. Survival in elderly patients receiving second-line therapy remains poor, and the 24-month cost of all care exceeds $97, 000. Patients would benefit from improved treatment options.